Optimization of a CH3NH3SnI3 based lead-free organic perovskite solar cell using SCAPS-1D simulator - Rana, Md. Sohel; Abdur Razzak, Md. (Institute of Advanced Engineering and Science, 2024)
In this study, a CH3NH3SnI3-based perovskite PV cell with the structure (FTO/TiO2/CH3NH3SnI3/Cu2O) was made and optimized by changing the layer thickness, defect density, and doping profile using the solar cell capacitance simulator (SCAPS) 1D simulator. To better understand how the device interface affects carrier dynamics, a synergic optimization of the device is done by altering the electron-transport layer (ETL) and hole-transport layer (HTL) materials. The light glows through the window layer of Sn2O: F, which serves as the transparent conducting oxide layer in our suggested cell construction and then travels over TiO2 as an n-type ETL. Due to its unique features, the p-type perovskite (CH3NH3SnI3) is chosen as the primary absorber layer. Lastly, Cu2O is added as an HTL before the back contact because it has a higher hole conductivity and the proper offsets for spreading the valance and conduction bands. Additionally, Cu2O-based devices outperform frequently utilized spiro-OMeTAD-based devices in terms of efficiency. According to the findings of these simulations, the optimized structure has a power conversion efficiency (PCE) of 41%, an open-circuit voltage of 1.32 V, a short-circuit current density of 34.31 mA/cm2 and a fill factor (FF) of 90.5%. Additionally, the optimized structure has a short-circuit current density of 34.31 mA/cm2.